ANALISIS DIFERENSIASI: PERSEPSI KEADILAN ORGANISASI PADA DOSEN INSTITUT AGAMA ISLAM NEGERI TAKENGON - Farid Fauzi (re-JIEM (Research Journal of Islamic Education Management), 2022)
Perceptions of organizational justice are often justified in different ways by each lecturer from all higher education institutions, especially at the Takengon State Islamic Institute. This study will examine the level of differentiation in the perception of organizational justice based on the demographic characteristics of the lecturers of the Takengon State Islamic Institute. The population in this study amounted to 141 with a sample of 59 lecturers whose sampling technique used simple random sampling. The research approach used is quantitative with non-parametric statistical analysis methods. Based on the results of the study, it can be found a level of differentiation of organizational justice based on the predictor of gender with a significance value of 0.034. Meanwhile, the predictors of demographic characteristics of age, tenure, position status, education level, and employment status did not have a significant level of differentiation with values ​​of 0.408, 0.432, 0.468, 0.331, and 0.791. It can be concluded that the predictor of gender has a significant level of differentiation from the perception of organizational justice of the lecturers of the Takengon State Islamic Institute.